Abiotic and biotic effects on secondary sexual traits at the population and individual levels in a passerine bird - Järvistö, Pauliina E. (fi=Turun yliopisto|en=University of Turku|, 2016)
Sexual selection is a major evolutionary force that may lead to changes in morphology, behaviour, mating systems, life history evolution and even speciation and extinction. In this thesis, I studied how abiotic and biotic factors affect fitness, and the expression and evolution of secondary sexual traits of pied flycatcher (Ficedula hypoleuca) individuals with variable dichromatic plumage colouration. I studied these questions using long-term data sets as well as manipulative and interspecific approaches. First, I studied whether the temperature-dependent breeding success of pied flycatcher males with different dorsal plumage colouration is due to the effects of the genotype of offspring or due to post-hatching paternal effects. Additionally, I investigated how increased or decreased parental effort affected future fitness of adult pied flycatchers, and the future expression of male sexual ornamentation. Furthermore, I examined the effects of environmental conditions experienced during the wintering season (in sub-Saharan Africa) on the expression of male secondary sexual traits, and the potential interactive effects between wintering conditions and male secondary sexual traits on future fitness of male and female pied flycatchers. Finally, I studied the possible effects of social environment on the development and signalling functions of male ornamental traits. I found that offspring raised by black pied flycatcher males were lighter than offspring raised by brown males when it was cold, and that this temperature-dependent breeding success of males with different dorsal plumage colouration was due to post-hatching paternal effects. Moreover, I found a plastic melanin response in dorsal plumage colouration of young males experiencing brood enlargement so that males became darker in the following breeding season. On the other hand, females that experienced brood enlargement had a significantly lower local survival in the next breeding season than those females in the control or in the reduced treatment group. I discovered that mean rainfall during the wintering season and winter NAO (North Atlantic Oscillation) index predicted both a plastic response and short-term microevolution on the wing patch size. The wing patch size of individuals decreased in winters of low precipitation and high NAO values, while in the same conditions individuals with a small wing patch seemed to suffer lower local survival than individuals with a large wing patch, and vice versa. I also found that males breeding in our study area became darker after dry and windy wintering conditions compared to moist and less windy wintering conditions. Moreover, after dry and windy wintering conditions females mated with large-patched males laid large clutches, whereas females mated with small-patched males laid small clutches after such wintering conditions. In addition, females paired with large-patched males after dry and windy wintering conditions had a higher probability of returning in the next breeding season than those that chose small-patched males after such conditions. I reveal that the forehead patch size of pied flycatcher males affects the outcome of intraspecific male-male competition. Moreover, in interspecific male-male competition between pied flycatcher males and collared flycatcher (Ficedula albicollis) males (a closely related sister species) it seems that the brown pied flycatcher males mimic females of collared flycatchers. This most likely leads to reduced aggression from more dominant collared flycatcher males. The results of this thesis provide important novel information on how changing environment affects phenotype expression and evolution as well as phenotype-dependent selection in the pied flycatcher. It seems to be that to a great extent the individual, population and year variations of expressed male secondary sexual traits of pied flycatchers are maintained by fluctuating environmental conditions experienced during the breeding and wintering seasons. Thus, global climate change can affect the population dynamics of long-distance migratory species in many and various ways. Climate change can take very different directions on the two different continents where breeding and wintering take place. Such environmental changes may have strong influences on the direction of sexual selection, on the expression of secondary sexual traits and on geno-/phenotype-dependent fitness, and all these processes shape populations.

Sukupuolivalinta on voimakas evolutiivinen voima, joka voi vaikuttaa eliöiden rakenteisiin, käyttäytymiseen ja elinkiertoekologiaan sekä jopa lajiutumis- ja sukupuuttoonkuolemisprosesseihin. Tässä väitöskirjassa tarkastelin, miten eloton sekä elollinen ympäristö vaikuttavat toissijaisten sukupuoliominaisuuksien ilmentämiseen ja evoluutioon kirjosiepolla (Ficedula hypoleuca). Tutkin näitä kysymyksiä käyttäen sekä pitkäaikaisaineistoja että manipulatiivisia ja vertailevia lähestymistapoja. Ensiksi tutkin, johtuuko eriväristen kirjosieppokoiraiden lämpötilasidonnainen lisääntymismenestys eroista poikasten perimässä vai eroista eriväristen koiraiden jälkeläishoidossa. Lisäksi tutkin, miten kasvatettu tai pienennetty poikuekoko vaikutti aikuisten lintujen tulevaan kelpoisuuteen sekä koiraiden toissijaisten sukupuoliominaisuuksien ilmentämiseen seuraavana lisääntymiskautena. Seuraavaksi tarkastelin talvehtimisalueiden (Saharan eteläpuoleinen Afrikka) ympäristöolosuhteiden vaikutusta koiraiden toissijaisten sukupuoliominaisuuksien ilmentämiseen, sekä mahdollisia talvehtimisolosuhteiden ja koiraiden fenotyypin välisiä yhdysvaikutuksia koirasja naaraskirjosieppojen kelpoisuuteen. Lopuksi tutkin sosiaalisen ympäristön mahdollisia vaikutuksia koiraiden toissijaisten sukupuoliominaisuuksien kehittymiseen. Kylmällä säällä mustien koiraiden kasvattamat poikaset olivat kevyempiä kuin ruskeiden koiraiden kasvattamat poikaset. Tämä eriväristen koiraiden lämpötilasidonnainen lisääntymismenestys johtui eriväristen koiraiden eroista hoitaa poikasia eri lämpötiloissa. Lisäksi löysin yksilönsisäisen vasteen melaniinivärityksessä niillä koirailla, joiden poikuekokoa oli kasvatettu niin, että koirasyksilöt tummenivat seuraavana lisääntymiskautena. Toisaalta, niillä naarailla, joiden poikuekokoa oli kasvatettu, oli pienempi todennäköisyys palata seuraavalle lisääntymiskaudelle kuin niillä naarailla, joiden poikuekokoa oli pienennetty tai ei ollut muutettu. Talvehtimiskauden keskisademäärä sekä talvi-NAO (North Atlantic Oscillation) vaikuttivat koirasyksilöiden siipilaikun kokoon sekä siipilaikun koosta riippuvaan valintaan. Yksilöiden siipilaikun koko pieneni vähäsateisina korkean NAO:n talvina. Samojen olosuhteiden aikana pienilaikkuisilla koirailla oli alhaisempi elossasäilyvyys kuin suurilaikkuisilla koirailla, kun taas kosteiden, alhaisen NAO:n, talvina tilanne oli päinvastainen. Lisäksi koiraat sulkivat tummemman höyhenpuvun kuivien talvehtimisolosuhteiden aikana verrattuna kosteisiin talvehtimisolosuhteisiin. Havaitsin myös, että naaraat, jotka pariutuivat suurisiipilaikkuisen koiraan kanssa kuivan talven jälkeen munivat suurempia munalukuja kuin ne, jotka pariutuivat pienilaikkuisen koiraan kanssa. Lisäksi havaitsin, että kuivan talven jälkeen niillä naarailla, jotka pariutuivat suurisiipilaikkuisen koiraan kanssa, oli korkeampi elossäsäilyvyys kuin niillä, jotka pariutuivat pienilaikkuisen kanssa. Tulosteni mukaan otsalaikun koko vaikuttaa lajinsisäisen koiras-koiraskilpailun lopputulokseen niin, että suurilaikkuiset koiraat olivat pienilaikkuisia aggressiivisempia. Lisäksi näyttäisi siltä, että lajienvälisessä koiras-koiraskilpailussa kirjosieppokoiraiden ja sepelsieppokoiraiden (Ficedula albicollis, sisarlaji) välillä ruskeat kirjosieppokoiraat mimikoivat sisarlajinsa naaraita. Tämä todennäköisesti vähentää sepelsieppokoiraiden aggressiivisuutta kirjosieppokoiraita kohtaan. Väitöskirjani tulokset tarjoavat uutta tärkeää tietoa siitä, miten muuttuva ympäristö vaikuttaa fenotyypin ilmentämiseen ja evoluutioon sekä fenotyypistä riippuvaan valintaan kirjosiepolla. Tulosteni perusteella vaikuttaa siltä, että yksilön- ja populaationsisäistä sekä vuosien välistä vaihtelua toissijaisten sukupuoliominaisuuksien ilmentämisessä ylläpitävät suurelta osin vaihtelevat ympäristöolosuhteet sekä lisääntymis- että talvehtimisalueilla. Siten mailmanlaajuinen ilmastonmuutos voi vaikuttaa pitkänmatkan muuttolajin populaatiodynamiikkaan monella eri tavalla. Ilmasto voi muuttua hyvin eri tavalla kahdella eri mantereella, jolla lisääntyminen ja talvehtiminen tapahtuvat. Tällaiset ympäristönmuutokset voivat vaikuttaa hyvin voimakkaasti sukupuolivalinnan suuntaan, toissijaisten sukupuoliominaisuuksien ilmentämiseen sekä fenotyypiltään erilaisten yksilöiden kelpoisuuteen, ja kaikki nämä prosessit osaltaan muokkaavat populaatioita.